The Therapeutic and Diagnostic Potential of Amyloid β Oligomers Selective Antibodies to Treat Alzheimer’s Disease - Viola, Kirsten L.; Bicca, Maira A.; Bebenek, Adrian M.; Kranz, Daniel L.; Nandwana, Vikas; Waters, Emily A.; Haney, Chad R.; Lee, Maxwell; Gupta, Abhay; Brahmbhatt, Zachary; Huang, Weijian; Chang, Ting-Tung; et al. (Frontiers in Neuroscience, 2022)
Improvements have been made in the diagnosis of Alzheimer's disease (AD), manifesting mostly in the development of in vivo imaging methods that allow for the detection of pathological changes in AD by MRI and PET scans. Many of these imaging methods, however, use agents that probe amyloid fibrils and plaques - species that do not correlate well with disease progression and are not present at the earliest stages of the disease. Amyloid β oligomers (AβOs), rather, are now widely accepted as the Aβ species most germane to AD onset and progression. Here we report evidence further supporting the role of AβOs as pathological instigators of AD and introduce promising anti-AβO diagnostic probes capable of distinguishing the 5xFAD mouse model from wild type mice by PET and MRI. In a developmental study, Aβ oligomers in 5xFAD mice were found to appear at 3 months of age, just prior to the onset of memory dysfunction, and spread as memory worsened. The increase of AβOs is prominent in the subiculum and correlates with concomitant development of reactive astrocytosis. The impact of these AβOs on memory is in harmony with findings that intraventricular injection of synthetic AβOs into wild type mice induced hippocampal dependent memory dysfunction within 24 hours. Compelling support for the conclusion that endogenous AβOs cause memory loss was found in experiments showing that intranasal inoculation of AβO-selective antibodies into 5xFAD mice completely restored memory function, measured 30-40 days post-inoculation. These antibodies, which were modified to give MRI and PET imaging probes, were able to distinguish 5xFAD mice from wild type littermates. These results provide strong support for the role of AβOs in instigating memory loss and salient AD neuropathology, and they demonstrate that AβO selective antibodies have potential both for therapeutics and for diagnostics.